SEMI-ANALYTICAL SPACECRAFT DYNAMICS AROUND PLANETARY MOONS - Cardoso dos Santos, J. [UNESP]; Carvalho, J. P. S.; Vilhena de Moraes, R.; Prado, A. F. B. A.; Majji, M.; Turner, J. D.; Wawrzyniak, G. G.; Cerven, W. T. (Univelt Inc, 2016)
Several missions that propose to explore systems of planetary moons will require high-inclined orbits for gravity and surface mapping. In this context, this work aims to perform a search for these orbits considering gravitational disturbances on a spacecraft's orbit around different planetary moons. An analytical model for the third-body perturbation is developed, considering it in an eccentric-inclined orbit. The non-sphericity of some planetary moons is also considered. The dynamic of these orbits is explored by numerical simulations. The results satisfied the requirements for missions and complement the analytical studies found in the literature. Several orbits with inclinations in the order of 60 are found, which are below the critical inclination but still gives a good coverage.